The Economic Cost of Carbon Abatement with Renewable Energy Policies - Jan Abrell; Mirjam Kosch; Sebastian Rausch (ETH Zurich, CER-ETH - Center of Economic Research, 2017)
This paper exploits the randomness and exogeneity of weather conditions to identify the economic cost of decarbonization through renewable energy (RE) support policies. We find that both the aggregate cost and the distribution of cost between energy producers and consumers vary significantly depending on which type of RE technology is promoted reflecting substantial heterogeneity in production cost, temporal availability of natural resources, and market conditions (i.e., time-varying demand, carbon intensity of installed production capacities, and opportunities for cross-border trade). We estimate that the cost for reducing one ton of CO2 emissions through subsidies for solar are EUR 500-1870. Subsidizing wind entails significantly lower cost, which can even be slightly negative, ranging from EUR 5-230. While the economic rents for energy producers always decrease, consumers incur three to five times larger costs when solar is promoted but gain under RE policies promoting wind.
Keywords: Q28; Q48; Q54; L94; C01; 330; Decarbonization; Renewable Energy Policies; Wind; Solar; Electricity; Economic Cost; Distributional impacts